High-grade serous carcinoma of unknown primary origin associated with STIC clinically presented as isolated inguinal lymphadenopathy: a case report - Giancontieri, Paola; Turetta, Camilla; Barchiesi, Giacomo; Pernazza, Angelina; Pignataro, Gemma; D’Onghia, Giuliano; Santini, Daniele; Tomao, Federica (Frontiers in Oncology, 2024)
Serous tubal intraepithelial carcinoma (STIC) is a precancerous lesion of high-grade serous ovarian carcinoma (HGSOC). Usually, it arises from the fimbrial end of the tube, and it is associated with metastatic potential. On average, time to progression from STIC to HGSOC is 6.5 years. Therefore, whenever a STIC lesion is found, surgical staging and prophylactic salpingectomy are recommended in order to prevent an ovarian cancer. We’re reporting a rare case of a 45 years-old female patient who clinically presented an isolated right inguinal lymphadenopathy. The remaining clinical examination was normal. Therefore, an excisional biopsy of the lymph node was performed. Pathological analysis revealed a high-grade serous carcinoma, most likely of gynecological origin. Due to histological evidence, Computed Tomography (CT) scan was carried out. There was no CT evidence of ovarian disease, pelvic involvement, intra- abdominal lymphadenopathies, metastatic disease or ascites. All tumor markers resulted negative. The patient underwent laparoscopic hysterectomy and bilateral salpingo-oophorectomy followed by surgical staging. Surprisingly, pathological examination showed a STIC lesion in the fimbria of the left fallopian tube. This rare case aims to report the potential capability of STIC to spread particularly through lymphatic pathways rather than peritoneal.